2016
DOI: 10.2527/jas.2016-0621
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for both a liver damage phenotype caused by Fasciola hepatica and antibody response to Fasciola hepatica phenotype in dairy and beef cattle1

Abstract: is a helminth parasite of economic importance to the global cattle industry, with documented high international herd prevalence. The objective of the present study was to generate the first published genetic parameter estimates for liver damage caused by as well as antibody response to in cattle. Abattoir data on the presence of live , or -damaged livers, were available between the years 2012 and 2015, inclusive. A second data set was available on cows from 68 selected dairy herds with a blood ELISA test for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Twomey et al (2016) undertook a similar EBV validation exercise based on cows divergent in parental average EBV for liver fluke. The area reported under the receiver operating curver reported by Twomey et al (2016) was 0.522, with cows in the top (i.e., worst) 10% being 1.28 (95% CI = 1.05-1.36) times more likely to have livers damaged by liver fluke compared with contemporaries in the bottom (i.e., best) 10%. This difference in odds translated to a 6% unit probability difference between the top and bottom 10% of cows in the study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twomey et al (2016) undertook a similar EBV validation exercise based on cows divergent in parental average EBV for liver fluke. The area reported under the receiver operating curver reported by Twomey et al (2016) was 0.522, with cows in the top (i.e., worst) 10% being 1.28 (95% CI = 1.05-1.36) times more likely to have livers damaged by liver fluke compared with contemporaries in the bottom (i.e., best) 10%. This difference in odds translated to a 6% unit probability difference between the top and bottom 10% of cows in the study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Only data from dairy herds were considered further. A herd was classified as beef or dairy based on the average breed composition of the cows, as per Twomey et al (2016). Cow breed composition was determined from the recorded breed composition of ancestors.…”
Section: Datamentioning
confidence: 99%
“…For dairy and beef cattle in Ireland grassland systems, Mc-Clure et al (2014) used a binary trait definition and estimated a lower heritability of 0.15 for the presence of liver flukes (F. hepatica). Twomey et al (2016) reported a smaller heritability, in the range from 0.01 and 0.09, for the binary traits liver damage caused by F. hepatica and antibody response to F. hepatica in Irish dairy and beef cattle. Threshold models for categorical endoparasite traits with 2 or more classes were also applied by Passafaro et al (2015).…”
Section: Heritabilities and Genetic And Phenotypic Correlations For Ementioning
confidence: 96%
“…Milk production (Charlier et al, 2005;Mezo et al, 2011), reproductive performance Haddad et al, 2005;Charlier et al, 2007), and meat yield (Barling et al, 2000;Charlier et al, 2009a) have all been documented as compromised in cattle herds infected with Fasciola hepatica, Ostertagia ostertagi, or Neospora caninum. The high prevalence of infection in cattle with both F. hepatica and O. ostertagi (Sekiya et al, 2013;Twomey et al, 2016) suggests that current control practices (e.g., anthelmintic treatment; Bloemhoff et al, 2014) are sub-optimal. On the other hand, effective N. caninum control strategies (i.e., herd biosecurity and the culling of infected animals; Dubey et al, 2007) can be costly.…”
Section: Introductionmentioning
confidence: 99%
“…Using animal-level data for F. hepatica-damaged livers on >95,000 Irish dairy and beef cattle, Twomey et al (2016) reported the presence of significant underlying genetic variability suggesting that breeding strategies could be used as a supplementary control for F. hepatica. A limited number of studies exist in cattle that documented genetic parameters for phenotypes based on the other two endo-parasites of interest, O. ostertagi (n = 2; Morris et al, 2003;Coppieters et al, 2009) and N. caninum (n = 1; Pan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%